INFLUENCE OF CALCIUM CHANNELS BLOCKADE ON NEUROLOGICAL DISORDERS EXPRESSION AND MORTALITY RATE OF ANIMALS IN EXPERIMENTAL HEMORRHAGIC STROKE - Gozhenko, A.I.; Vastyanov, R.S.; Rodinsky, O.G.; Bibikova, V.M.; Yermuraki, P.P.; Ilina-Stohnienko, V.Yu. (World of Medicine and Biology, 2022)
The purpose of the study was to investigate the relationship between the mortality of experimental animals and methods of neurological status studying, behavioural and cognitive disorders in the dynamics of primary and recurrent hemorrhagic stroke and this pathological state pharmacological correction using calcium channel blockers. Two models of local stroke were used in the studies: the model of acute and repeated hemorrhagic stroke. The article analyzes and compares the mortality rates of experimental animals with the use of various methods of studying primary and recurrent hemorrhagic stroke. We studied and analyzed the dynamics of changes in mortality during the study of neurological status, behavioural and cognitive disorders and performed statistical analysis of animal mortality at different stages of the experiment, which correlated with the severity of neurological disorders and depth, dynamics of primary and recurrent hemorrhagic strokes. It was found that animal mortality depends on the method of hemorrhagic stroke reproduction and its reduction correlates with spontaneous partial recovery of impaired motor function and neurological status in the dynamics and is corrected by medication with calcium channel blockers. Authors demonstrated hemorrhagic stroke-induced animal’s mortality dependence on the pathogenetically based pharmacocorrection. The data received might be considered as an experimental background of reasonability of calcium channels blockers effects testing in clinical conditions at hemorrhagic strokes.
Keywords: primary hemorrhagic stroke; recurrent hemorrhagic stroke; mortality; neurological deficit; behavioural changes; memory disturbances; calcium channel blockade